Pendampingan Pemasaran Produk Unggulan Daerah Wajik Tapai Melayu Riau Untuk Menembus Pasar Ekspor - Sri Maryanti; Nining Sudiar; Afred Suci; Hardi Hardi (STKIP Andi Matappa, 2021)
The purpose of this community service activity is so that the products produced by Puspa Melayu partners are able to penetrate the export market, considering the sale of this wajik tapai Melayu product to be outside of Pekanbaru city. So far, many food products from outside countries that enter Indonesia reach 4-5%. The methods used in this activity are testing and evaluating wajik tapai Melayu, mentoring, and evaluation of wajik tapai Melayu product packaging as well as marketing workshops using social media. As a result, wajik tapai melayu can be exported because it can last a period of 1 (one) year, the packaging of wajik tapai Melayu products has met export standards that are not easily dented, and partners have been able to use social media for marketing its products such as Facebook, Instagram, JualBuy, and Shopee. The impact of this activity is that the net profit of malay tapai diamonds increased from the year before the community service activity increased to Rp. 516,096,000 - monthly.